THE INFLUENCE OF RENSIA SANVIRA TIKTOK ACCOUNTS FOR PARENTS INFORMING CHARACTER STRENGTHENING OF CHILDREN AGED 2 TO 6 YEARS OLD - Salsa Nur Haliza; Putty Anggie Septiani; Wahyunengsih (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This study aims to find out whether Rensia Sanvira's TikTok content affects character strengthening in children aged 2-6 years. In this study, the authors took the data by filling out a questionnaire with closed answers using google Forms. The object of the study is parents (born 1980-1999) who looked at Rensia Sanvira TikTok content and had children aged 2-6 years, with a total of 26 people. The research method used in research is a qualitative research method, with the approach used in the study being the content analysis approach. Based on the author's research, it can be divided into two parents who see Rensia Sanvira content (73.1%) and who do not see Rensia Sanvira content (26.9%). The results of filling out the questionnaire (94.7%) get a method of strengthening character in children through Rensia Sanvira content (94.7%). The technique given by Rensia Sanvira, through its content, affects the development of supporting the nature of children at home. Rensia Sanvira suggests character strengthening education in children through its content, namely: 1) Maintaining good communication and 2) Having an attitude of respect towards children. Based on the research results that the author conducted, it can be concluded that Rensia Sanvira TikTok content helps and affects the strengthening of the character of children aged 2-6 years who uphold the values of kindness make children have good morals and ethics for further personal development.